2009
DOI: 10.1161/atvbaha.109.184549
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein–Kinin System in Neovascularization

Abstract: T he formation of new blood vessels is viewed completely differently by cardiologists than by oncologists and ophthalmologists. Whereas the former try to stimulate this process, the latter put all efforts into blocking it. In any case, factors involved in neovascularization are of highest therapeutic relevance. The article by Stone et al in this issue of ATVB 1 corroborates that the kallikrein-kinin system (KKS) is one very important but yet underestimated player in this process. This peptide hormone system ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…While a few studies have found increased VEGF expression in cord blood [ 52 ] and cerebrospinal fluid [ 53 ], others have found either no difference in cerebrospinal fluid VEGF levels between asphyxiated and healthy newborns [ 54 ] or lower serum VEGF expression in severely asphyxiated compared to healthy newborns [ 55 ]. In the present study, KLK-5 expression was reduced in all asphyxiated newborns; KLK-5 promotes extracellular matrix degradation and neovascular sprouting by increasing MMP-9 activity, which, as previously noted, may contribute to brain injury [ 40 , 56 ]. Decreased KLK-5 expression may therefore represent another possible mechanism of neuroprotection or neurorestoration.…”
Section: Discussionsupporting
confidence: 81%
“…While a few studies have found increased VEGF expression in cord blood [ 52 ] and cerebrospinal fluid [ 53 ], others have found either no difference in cerebrospinal fluid VEGF levels between asphyxiated and healthy newborns [ 54 ] or lower serum VEGF expression in severely asphyxiated compared to healthy newborns [ 55 ]. In the present study, KLK-5 expression was reduced in all asphyxiated newborns; KLK-5 promotes extracellular matrix degradation and neovascular sprouting by increasing MMP-9 activity, which, as previously noted, may contribute to brain injury [ 40 , 56 ]. Decreased KLK-5 expression may therefore represent another possible mechanism of neuroprotection or neurorestoration.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, following ischaemia induced by severing the femoral artery, blood flow was restored after 3 weeks in wt but not in ko-B 1 mice, the latter showing a high incidence of limb necrosis suggesting the B 1 receptor as integral towards promoting neovascularization and angiogenesis (29,30). In another murine model, apolipoprotein (Apo) E and B 1 double ko animals showed a greater incidence of atherosclerotic plaque development and aneurysm than animals with ApoE ko alone, supporting further an antiatherogenic role for kinin B 1 receptors (31).…”
Section: Physiological Responsementioning
confidence: 99%
“…Assembly of contact factors in the presence of Zn 2? ions on endothelial cells results in the release of BK, which, through the action of its receptors, stimulates cell migration and proliferation by increasing the concentration of angiogenic mediators [34,126,127]. In addition, BK was recently shown to enhance the homing of circulating endothelial progenitor cells, a mechanism also important in forming new blood vessels [128].…”
Section: Angiogenesismentioning
confidence: 99%